Transterm: a database of mRNAs and translational control elements - Jacobs, Grant H. (Oxford University Press, 2002)
Transterm is a database that facilitates studies of translation and the translational control of protein synthesis. It contains a curated collection of elements in mRNAs that control translation, and biologically relevant mRNA regions extracted from GenBank. It is organised largely on a taxonomic basis with files and summaries for each species. Global patterns that may affect translation in particular species, for example bias in the context of initiation codons (Kozak’s consensus or Shine–Dalgarno sequences) or termination codons, can be detected in the consensus and information content bias summaries. Several types of access are provided via a web browser interface. Transterm defined elements may be matched in a user’s sequence or in the database. Alternatively, elements can be entered by the user to search specific sections of the database (for example, coding regions or 3′ flanking regions or the 3′-UTRs) or the user’s sequence. Each Transterm defined element has an associated biological description with references. The database is accessible at http://uther.otago.ac.nz/Transterm.html.